Time Correlation Laws Inferred from Climatic Records: Long-Range Persistence and Alternative Paradigms - Lanfredi, Maria; Simoniello, Tiziana; Cuomo, Vincenzo; Macchiato, Maria (IntechOpen, 2011)
None